(3hLgI fXQ GdfbOjjfs - (3HGQj(B, (3SjLds ((3GdQjGV(B:s (3OGQ GdeQjN(B,s, 1987)
(3GdfbhO heTGcd GdGbJUGO GdfbOj, GdCShGb GdeGdjI hGdeDSSGJ GdeGdjI, YedjI YQV GdfbhO, GdHfc GdeQcRj, GSJQGJjLjI GdSjGSI GdfbOjI, SYQ GdaGFOI hfXQjI GdONd, GdJVNe(B: (3GdCSHGH hGdfJGFL, hLgGJ fXQ LOjOI Yf SjGSGJ GdGSJbQGQ(B.s
Keywords: (3GdCShGb GdeGdjIs; (3GdEbJUGO GdeGdjs; (3GdHfhcs; (3GdJVNes; (3GdfbhOs